2020
DOI: 10.2147/ott.s242703
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Protective Effect of Testosterone on the Ovarian Reserve During Cyclophosphamide Treatment</p>

Abstract: Introduction: Cyclophosphamide, which is widely used to treat malignant disease, causes ovarian follicular atresia, which leads to premature ovarian insufficiency. The present study evaluated the protective effect of testosterone in preventing the decline in the ovarian reserve during cyclophosphamide treatment. Methods: Using the COV434 human granulosa cell line, the protective effect of testosterone against cyclophosphamide was evaluated by immunocytochemistry, Western blotting and an MTS assay. The follicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The observed higher levels of AMH in 75 and 100 mg/kg CPA groups on day 4, and continuously higher in 100 mg/kg CPA group till day 12, might also support plausible primordial follicle activation after CPA in vivo treatment (20)(21)(22)(23). This is not contradictory to the observation of reduced serum AMH levels by CPA treatment in studies in vivo (26,27). Overactivation in vivo can initially lead to follicles sense through molecular communications and induce enhanced secretion of AMH to inhibit further overactivation through a paracrine regulation (28)(29)(30).…”
Section: Discussionsupporting
confidence: 57%
“…The observed higher levels of AMH in 75 and 100 mg/kg CPA groups on day 4, and continuously higher in 100 mg/kg CPA group till day 12, might also support plausible primordial follicle activation after CPA in vivo treatment (20)(21)(22)(23). This is not contradictory to the observation of reduced serum AMH levels by CPA treatment in studies in vivo (26,27). Overactivation in vivo can initially lead to follicles sense through molecular communications and induce enhanced secretion of AMH to inhibit further overactivation through a paracrine regulation (28)(29)(30).…”
Section: Discussionsupporting
confidence: 57%
“…For example, early menopause associated with smoking may be ascribed partially to decreased estrogen due to smoking 11 . Although excess androgen was considered detrimental to women's fertility, recent studies have shown that androgen could attenuate follicular atresia 12,13 . We previously observed that shorter sleep duration on weekends was associated with higher total and free testosterone levels among premenopausal Japanese women with regular menstrual cycles; the mean testosterone levels were 26.7 ng/dL for ≤6 hours and 22.2 ng/dL for 8+ hours of sleep 14 .…”
mentioning
confidence: 94%
“…11 Although excess androgen was considered detrimental to women's fertility, recent studies have shown that androgen could attenuate follicular atresia. 12,13 We previously observed that shorter sleep duration on weekends was associated with higher total and free testosterone levels among premenopausal Japanese women with regular menstrual cycles; the mean testosterone levels were 26.7 ng/dL for ≤6 hours and 22.2 ng/dL for 8+ hours of sleep. 14 Therefore, there is a possibility that shorter sleep duration may be associated with later age at menopause.…”
mentioning
confidence: 95%
“…The clinical study illustrated that women suffering from cancer which treated with CPA can experience infertility due to various degrees of ovarian toxicity (3). The American Society of Clinical Oncology Guideline demonstrates that CPA therapy leads to ovarian failure or impaired infertility in the cancerous patients due to the apoptotic alternation in granulosa and theca cells followed by follicles demolition (4). It has been known that CPA could induce severe ovary damage and may cause premature ovarian failure (POF) due to ovarian toxicity by applying various mechanism including oxidative stress, in ammation, and apoptosis (5).…”
Section: Introductionmentioning
confidence: 99%